2016
DOI: 10.1111/jnu.12233
|View full text |Cite|
|
Sign up to set email alerts
|

Recommendations of Common Data Elements to Advance the Science of Self‐Management of Chronic Conditions

Abstract: Purpose Common data elements (CDEs) are increasingly being used by researchers to promote data sharing across studies. The purposes of this article are to (a) describe the theoretical, conceptual, and definition issues in the development of a set of CDEs for research addressing self-management of chronic conditions; (b) propose an initial set of CDEs and their measures to advance the science of self-management; and (c) recommend implications for future research and dissemination. Design and Methods Between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 34 publications
1
58
0
1
Order By: Relevance
“…Through a consensus process, the CDE Working Group reviewed, agreed on, and developed a set of CDEs to be commonly collected in all symptom studies–sleep, fatigue, pain, and cognitive or affect–regardless of diagnosis (Redeker et al, 2015), and to evaluate self-management of these symptoms (Moore et al, 2016)…”
Section: Common Data Elementmentioning
confidence: 99%
“…Through a consensus process, the CDE Working Group reviewed, agreed on, and developed a set of CDEs to be commonly collected in all symptom studies–sleep, fatigue, pain, and cognitive or affect–regardless of diagnosis (Redeker et al, 2015), and to evaluate self-management of these symptoms (Moore et al, 2016)…”
Section: Common Data Elementmentioning
confidence: 99%
“…A variety of assessment modalities, including online assessments via consumer portals and EHR, tablet computers that integrate with EHR, text messaging, web-based tools, automated telephone follow-up, and remote monitoring tools can be used (77,149-152). Selecting validated tools, used for assessment and ongoing evaluation, will generate more evidence to support DSMES (153). Although not an exhaustive list or applicable to all populations, examples of assessment tools can be found in the Standards' glossary ( Table 1).…”
Section: Standard 7 Individualizationmentioning
confidence: 99%
“…These questions were developed for this study. They are modeled after Lorig et al and the PROMIS database (patient‐reported outcomes measurement information system) and adapted for this population (Lorig & Holman, 2003; Moore et al, 2016; PROMIS, 2016). The two family member participants respond independently using a scale of 0–10 where a score of zero represents being not at all confident and a score of 10 represents being extremely confident.…”
Section: Methodsmentioning
confidence: 99%